2020
DOI: 10.1029/2019ja027455
|View full text |Cite
|
Sign up to set email alerts
|

Local Time Asymmetries in Jupiter's Magnetodisc Currents

Abstract: We present an investigation into the currents within the Jovian magnetodisc using all available spacecraft magnetometer data up until 28 July 2018. Using automated data analysis processes as well as the most recent intrinsic field and current disk geometry models, a full local time coverage of the magnetodisc currents using 7,382 lobe traversals over 39 years is constructed. Our study demonstrates clear local time asymmetries in both the radial and azimuthal height‐integrated current densities throughout the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 38 publications
13
60
2
Order By: Relevance
“…Analyzing the equatorial magnetic field measurements of the whole Galileo mission, Lorch et al. (2020) also concluded that azimuthal currents play a key role in determining the location of the field‐aligned currents. Furthermore, Vogt et al.…”
Section: Six Pieces Of Evidence Against the “Corotation Enforcement” mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the equatorial magnetic field measurements of the whole Galileo mission, Lorch et al. (2020) also concluded that azimuthal currents play a key role in determining the location of the field‐aligned currents. Furthermore, Vogt et al.…”
Section: Six Pieces Of Evidence Against the “Corotation Enforcement” mentioning
confidence: 99%
“…It would consistently strengthen the total net field-aligned currents on the duskside and weaken the currents on the dawnside. Analyzing the equatorial magnetic field measurements of the whole Galileo mission, Lorch et al (2020) also concluded that azimuthal currents play a key role in determining the location of the field-aligned currents. Furthermore, Vogt et al (2019) noted that the dawn-dusk discrepancy on the bend-back angle is even larger during solar wind compressions, which should lead to a brightening of the dawn arc of the MEs but a dimming of the dusk arc if the corotation enforcement current were driving the main auroral emissions.…”
Section: Dawn/dusk Brightness Asymmetrymentioning
confidence: 99%
“…In the previous models, the current sheet is always assumed as a symmetric azimuthal (dawn-to-dusk direction) configuration while the current density decreases with the distance from the planet. However, from a detailed analysis by Lorch et al (2020), the current density varies with local time and the radial current should also be considered. So we employ the TS07 method (Tsyganenko & Sitnov, 2007) to construct the complex morphologies of the equatorial current system.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…However, from a detailed analysis by Lorch et al. (2020), the current density varies with local time and the radial current should also be considered. So we employ the TS07 method (Tsyganenko & Sitnov, 2007) to construct the complex morphologies of the equatorial current system.…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation